Proteomics based markers of clinical pain severity in juvenile idiopathic arthritis - Hanne Van Der Heijden; Benoit Fatou; Diana Sibai; Kacie Hoyt; Maria Taylor; Kin Cheung; Jordan Lemme; Mariesa Cay; Benjamin Goodlett; Jeffery Lo; Melissa M. Hazen; Olha Halyabar; et al. (BMC, 2022)
Highlights In the current preliminary study, serum proteins associated with pain severity were identified in JIA patients. Pain-associated proteins had functional roles predominantly in immune or inflammatory processes. Correlations of pain-associated proteins with ESR and altered CNS morphology were also observed with ESR and altered CNS morphology were also observed. Larger-scale as well as longitudinal studies are needed to determine if evaluation of the proteome may provide a platform for identifying novel analgesic targets in JIA.